Binding of Platelet Agglutinating Protein p 37 from the Plasma of a Patient with Thrombotic Thrombocytopenic Purpura to Human Platelets - Lian, Eric C-Y; Siddiqui, Farooq A (Thrombosis and Haemostasis, 1991)
We have previously reported the purification of a 37 kDa platelet agglutinating protein (PAP p37) from the plasma of a patient with thrombotic thrombocytopenic purpura (TTP) that was shown to be present in a subset of TTP patients. To gain further insight into the interaction between PAP p37 and platelets, we have studied the properties of PAP p37 binding to platelets. Washed human platelets from two normal donors and two TTP patients after recovery were used for the experiments. The PAP p 37 binding to platelets was specific, concentration dependent and saturable. Scatchard analysis demonstrated about 20,564–27,090 PAP p37 binding sites per platelet. Stimulation of platelets with thrombin or ADP did not have any significant effect on its binding.Thiol- and serine-specific protease inhibitors did not inhibit PAP p37 binding to the platelets. Sugars such as glucose, fructose, mannose, and sialic acid, at 40 mM, inhibited its binding to platelets by 44%, 73%, 79%, and 91% respectively, but galactose and amino sugars did not have any significant effect. At 250 μg/ml, Concanavalin-A inhibited 42% of binding, but other lectins, such as phytohemagglutinin-P, potato lectin and helix pomatia lectin (snail), did not. Pre-incubation of 125I-PAP p37 with the adult human IgG, decreased its binding to the platelets. The monoclonal antibodies to GP Ib (6D1) and GP IIb-IIIa complex (10E5) did not inhibit the binding of 125I-PAP p37 to platelets. Fibrinogen and von Willebrand factor did not affect the binding either. These results suggest that PAP p37 binds to platelets on the sites other than GP lb or GP IIb-IIIa complex.